Fixed-Point Theorem for Isometric Self-Mappings - Joseph Frank Gordon (International Journal of Mathematics and Mathematical Sciences)
In this paper, we derive a fixed-point theorem for self-mappings. That is, it is shown that every isometric self-mapping on a weakly compact convex subset of a strictly convex Banach space has a fixed point.